2018
DOI: 10.1111/cns.13066
|View full text |Cite
|
Sign up to set email alerts
|

A single factor induces neuronal differentiation to suppress glioma cell growth

Abstract: Summary Aim Glioma, with fast growth and progression features, is the most common and aggressive tumor in the central nervous system and is essentially incurable. This study is aimed at inducing neuronal differentiation to suppress glioma cell growth with a single transcription factor. Methods Overexpression of transcription factor SRY (sex determining region Y)‐box 11 (SOX11) and Zic family member 1 (ZIC1) was, respectively, performed in glioma cells with lentivirus infection. CRISPR/Cas9 technology was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Genetic loss of ATOH1 results in neurophysiological deficits, including a reduction in the size of the cerebellum and premature death due to dysregulated respiration resulting in apnea ( Rose et al, 2009 ). Like many bHLH TFs, ATOH1 itself is rarely mutated in brain tumors; its expression levels, however, are reported to be dysregulated in a number of brain tumor subtypes ( Fu et al, 2019 ). The role of ATOH1 in high-grade glioma has yet to be well-defined, although correlative relationships between high ATOH1 expression in the SHH-activated subtype of medulloblastoma have been reported ( Salsano et al, 2004 ).…”
Section: Lineage-specific Transcriptional Regulatorsmentioning
confidence: 99%
“…Genetic loss of ATOH1 results in neurophysiological deficits, including a reduction in the size of the cerebellum and premature death due to dysregulated respiration resulting in apnea ( Rose et al, 2009 ). Like many bHLH TFs, ATOH1 itself is rarely mutated in brain tumors; its expression levels, however, are reported to be dysregulated in a number of brain tumor subtypes ( Fu et al, 2019 ). The role of ATOH1 in high-grade glioma has yet to be well-defined, although correlative relationships between high ATOH1 expression in the SHH-activated subtype of medulloblastoma have been reported ( Salsano et al, 2004 ).…”
Section: Lineage-specific Transcriptional Regulatorsmentioning
confidence: 99%
“…Consistently, we also showed that activation of the interleukin (IL)‐6/Janus tyrosine kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) axis contributed to cAMP‐induced expression of the astrocytic biomarker glial fibrillary acidic protein (GFAP) in gliomas [16]. Interestingly, recent studies demonstrated that glioma cells could be directly reprogrammed into terminal‐differentiated neurons by either transduction of neuron‐specific transcriptional factors [17–20] or treating with a small molecule cocktail [21,22], suggesting that the differentiation fate of glioma cells is highly plastic and could be driven by different stimuli. However, the cAMP agonist‐induced differentiation pattern and the underlying mechanisms of glioma are still incompletely understood.…”
mentioning
confidence: 77%
“…Sall1 (Spalt-Like Transcription Factor 1), which is expressed specifically in microglia and is associated with microglial activation, suppresses glioma cell proliferation and migration and may work as a functional tumor suppressor gene in glioma 26 , 27 . Zic1 (Zic family member 1) is associated with the suppression of glioma cell growth 28 . Plxnb3 (plexin-B3) inhibits cell migration and invasion induced by stimulation with its ligand Sema5A 29 .…”
Section: Discussionmentioning
confidence: 99%